2007
DOI: 10.1074/jbc.m704524200
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Human 4F2hc Ectodomain Provides a Model for Homodimerization and Electrostatic Interaction with Plasma Membrane

Abstract: 4F2hc (CD98hc, FRP-1, and SLC3A2) is a multifunctional type II membrane glycoprotein involved in amino acid transport (1), cell fusion (2), and ␤1 integrin-dependent adhesion (3). 4F2hc and the homologous rBAT are the heavy subunits of the heteromeric amino acid transporters (HATs), 4 which are linked by a disulfide bridge to the catalytic light subunit (Fig. 1A). One of six light subunits (LAT1, LAT2, y ϩ LAT1, y ϩ LAT2, asc-1, and xCT) heterodimerizes with 4F2hc, thereby rendering a range of transport activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
114
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(121 citation statements)
references
References 51 publications
(45 reference statements)
6
114
1
Order By: Relevance
“…This result indicated that gB and gH interacted with CD98hc independently of each other and was in agreement with the previous report (17) on HSV-1 mutants lacking gB and/or gH. The fusion components for viral de-envelopment, which are probably induced at the nuclear membrane in HSV-1-infected cells, should include a host cell fusogenic protein(s) and perhaps cellular cofactor(s) such as CD98hc and ␤1 integrin, whose crystal structures have no structural homology with any known fusion proteins (52,53). This is suggested because (i) HSV-1 gB, the only viral fusogenic protein that has structural homology to a vesicular stomatitis virus fusion protein, glycoprotein G, plays only a minor role in viral de-envelopment fusion (17), as described above, and (ii) nuclear egress of the Drosophila cellular RNP complex may only require cellular fusion components at the nuclear membrane (3).…”
Section: Discussionsupporting
confidence: 77%
“…This result indicated that gB and gH interacted with CD98hc independently of each other and was in agreement with the previous report (17) on HSV-1 mutants lacking gB and/or gH. The fusion components for viral de-envelopment, which are probably induced at the nuclear membrane in HSV-1-infected cells, should include a host cell fusogenic protein(s) and perhaps cellular cofactor(s) such as CD98hc and ␤1 integrin, whose crystal structures have no structural homology with any known fusion proteins (52,53). This is suggested because (i) HSV-1 gB, the only viral fusogenic protein that has structural homology to a vesicular stomatitis virus fusion protein, glycoprotein G, plays only a minor role in viral de-envelopment fusion (17), as described above, and (ii) nuclear egress of the Drosophila cellular RNP complex may only require cellular fusion components at the nuclear membrane (3).…”
Section: Discussionsupporting
confidence: 77%
“…23 Indeed, 4F2hc serves, in addition to system y þ L, as the heavy subunit of five other amino acid transporters and has a role in b1-integrin function. 24 All the new mutations identified but two encode for severely truncated proteins, if translated, suggesting a dramatic loss of transport function in these cases. The novel large deletions (DelE6-E11 and DelE4-E11) were associated with the most severe phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…According to this model, 4F2hc-ED interacts with all the extracellular loops or ends of TMDs of LAT2. 4F2hc is N-glycosylated in Pichia (18) and mammalian cells (8), and in the model the four putative sites are located in the most external face of 4F2hc-ED, out of the contact interface with LAT2 (Fig. 2B).…”
Section: Significancementioning
confidence: 99%
“…The heavy subunits are type II membrane N-glycoproteins with a single transmembrane domain (TMD), an intracellular N terminus, and a large extracellular C terminus with sequence homology with bacterial α-amylases. Indeed, the atomic structure of the extracellular domain (ED) of human 4F2hc (4F2hc-ED) is similar to that of bacterial glucosidases [i.e., a triose phosphate isomerase barrel, (βα) 8 , (subdomain A) and eight antiparallel β-strands (subdomain C)] but lacks glucosidase activity (8). The conserved cysteine residue participating in the intersubunit disulfide bridge is located between the single TMD and 4F2hc-ED.…”
mentioning
confidence: 99%